An analysis of a spatial and economic structure in a region comprising the different kinds of competition - Toshiharu Ishikawa (European Regional Science Association (ERSA), 2002)
A country or a vast region usually comprises different kinds of spatial competition, a free-entry competition, imperfective competition, and a local monopoly, in its economic system: While many firms concentrate on a place and formulate the competitive market there, a same kind firm exists on another area and enjoys a local monopoly position on the market area. When the markets with different natures of competition are independent from each other economically as well as geographically, each market reveals a unique spatial and economic structures that are peculiar to the spatial competition in question. Since these spatial and economic structures have the obvious and typical characteristics, the existing theory of spatial economics may elucidate adequately these structures. In general, however, the markets are economically influenced each other in spite of being separated spatially. The spatial and economic structures of the markets are different from those of the markets isolated economically, and their structures may show the complicated features due to the affections from the other markets. In order to analyze these intricate structures successfully the model designed appropriately for this spatial system is needed. The purposes of the paper are, adopting the variant circumference model, to clarify the mechanism of interaction between the markets with the different kinds of competition and to analyze the spatial and economic structures generated on these markets in a region. This paper assumes the two kinds of competition, a quasi-perfect copetition and a local monopoly, and takes simultaneously goods and labor into the account in the analysis. Analyzing the market sizes and the commuting rages of the firms and the firms' profits, prices, and wage rates on the markets, the paper shows the spatial and economic structures established in the region comprising two different kinds of spatial competition.
Keywords: 330